ANALYSIS OF THE APPLICATION OF DIGITIZATION OF SAILING APPROVAL LETTERS IN CLEARANCE OUT ACTIVITIES (STUDY ON KSOP CLASS III LABUAN BAJO) - Putra, Fajar Kurnia; Rahmawati, Malidiah; Purwitasari, Diyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2025)
This research aims to find out whether there is a difference between the implementation of digitalization of shipping approval letters before and after the digitalspb.id website is implemented. The subjects of this research are stakeholders and service users (Steakholders) with a research sample of 30 people. This research data was collected by making direct observations while the researcher was carrying out land practice at the Labuan Bajo Class III Harbormaster and Port Authority Office. As well as the distribution method using the Goggle Form (Questionnaire) to measure implementation of the digitalization process. The method used is a quantitative method. Data analysis uses a paired sample T-Test. The results show that the average value after implementation is greater than the average value before implementation, this means that there is an increase in the results of digitalization after the digitalspb.id website was implemented. The research results also show that the significance obtained is 0.000, which is smaller than 0.05, or the value of the T-count with a value of 12.363 is greater than the T-table with a value of 2.045, thus Ho is rejected and Ha is accepted. This means that there is a significant difference in the results of implementing digitalization in the process of issuing shipping approval letters that have been implemented.